Tracking Photoinduced Charge Redistribution in a Cu(I) Diimine Donor–Bridge–Acceptor System with Time-Resolved Infrared Spectroscopy - Sean A. Roget; Wade C. Henke; Maxwell Taub; Pyosang Kim; Jonathan T. Yarranton; Xiaosong Li; Karen L. Mulfort; Lin X. Chen (Photochem)
Understanding electron density migration along excited-state pathways in photochemical systems is critical for optimizing solar energy conversion processes. In this study, we investigate photoinduced electron transfer (PET) in a covalently linked donor–bridge–acceptor (D-B-A) system, where [Cu(I)-bis(1,10-phenanthroline)]+ acts as an electron donor, and anthraquinone, tethered to one of the phenanthroline ligands via a vibrationally active ethyne bridge, behaves as an electron acceptor. Visible transient absorption spectroscopy revealed the dynamic processes occurring in the excited state, including PET to the acceptor species. This was indicated by the spectral features of the anthraquinone radical anion that appeared on a timescale of 30 ps in polar solvents. Time-resolved infrared (TRIR) spectroscopy of the alkyne vibration (CC stretch) of the ethyne bridge provided insight into electronic structural changes in the metal-to-ligand charge transfer (MLCT) state and along the PET reaction coordinate. The observed spectral shift and enhanced transition dipole moment of the CC stretch demonstrated that there was already partial delocalization to the anthraquinone acceptor following MLCT excitation, verified by DFT calculations. An additional excited-state TRIR signal unrelated to the vibrational mode highlighted delocalization between the phenanthroline ligands in the MLCT state. This signal decayed and the CC stretch narrowed and shifted towards the ground-state frequency following PET, indicating a degree of localization onto the acceptor species. This study experimentally elucidates charge redistribution during PET in a Cu(I) diimine D-B-A system, yielding important information on the ligand design for optimizing PET reactions.